Patterns of isotope uptake in sequential postoperative bone scan in undisplaced femoral-neck fractures - Yoon, Byung Ho (Springer Berlin Heidelberg, 2013)
PURPOSE: We aimed to investigate the changing pattern of isotope uptake in the sequential bone scan test for the prediction of osteonecrosis of the femoral head in patients with an undisplaced femoral-neck fracture. METHODS: Fifty-four cases of sequential bone scan for nondisplaced femoral-neck fracture treated by internal fixation with cannulated screws between 2000 and 2009 were retrospectively studied. The mean follow-up period was 4.2 years. The first postoperative bone scan was performed two weeks postoperatively in all patients. Second, third, and fourth follow-up bone scans were performed at one to six months, 12–18 months, and 18–24 months postoperatively. RESULTS: Mean femoral-head ratio (FHR) in the first postoperative bone scan was 0.99. Although it was under 1.0 in 38 patients (70.4 % of the 54 patients), only one patient developed osteonecrosis of the femoral head. The others showed hot uptake in their second follow-up bone scan. Mean FHRs in the second, third, and fourth postoperative bone scans were 1.69, 1.29, and 1.05, respectively, and there were significant statistical differences in each follow-up period (P = 0.035). In addition, there were unique patterns of isotope uptake with the passage of time, such as cold uptake in the early stage, hot uptake in a couple of months, and iso-uptake in the late stage. CONCLUSIONS: Early postoperative bone scan results should not be over interpreted when predicting osteonecrosis of the femoral head.